Effect of Extracts of Frozen-Thawed Heart Fragments on Rats - Rohoza, Liliya A.; Chizh, Mykola O.; Galchenko, Sergiy Ye.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2013)
The investigation was performed to reveal the influence of the extracts of frozen-thawed heart fragments of pigs and newborn piglets administered to young and aged rats on an organism in general and heart in particular. Administration of the extracts to young animals during 28 days was shown to increase the number of nuclei in the heart muscle unlike the mature rats, but did not affect the rate of changes in the weight of animals and their hearts. No effect of extracts on blood morphology and heart electrophysiological parameters was found. Probl Cryobiol Cryomed 2013; 23(1):91–98.